Consumer Response Analysis to Steamed Red Bean Flour Cake - Suni, Muh. Irdiansyah (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2022)
The title of this research is